DESIGN GAME PUZZLE UNTUK TINGKAT SEKOLAH DASAR MENGGUNAKAN ADOBE CC ANIMATE 2018 - Thang, John; Sari, Ria Eka (Institut Seni Indoensia Surakarta, 2022)
Playing is something that is very popular with children because playing is an activity that can build motor nerves and children's growth and development. Design of the puzzle game designed is a research based on a quantitative approach due to the transition from a pandemic to an endemic period after the decline in the spread of the covid-19 virus. This puzzle game is designed not only to provide games for elementary school children but also to increase the intelligence of thinking for these children. The design of this puzzle game uses quantitative data collection and 5W 1H analysis methods. The results of this game design can later be downloaded via the link provided.